2002
DOI: 10.1177/104973202129119847
|View full text |Cite
|
Sign up to set email alerts
|

“Unremarkable” Recoveries: Normalizing Adversity and Cancer Survival

Abstract: Much of the existing popular literature suggests that survival from life-threatening diseases encourages a process of self-transformation. Seventeen long-term survivors of metastatic cancer were interviewed about the impact of a life-threatening condition on their life stories. Contrary to the existing literature, which suggests such an event greatly transforms the individual, nearly all of those interviewed for this study framed their unusual recoveries as being largely unremarkable. Traditional North America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Ongoing stressors combine to worsen heart health and cause increased distress that must be controlled by "not worrying." "Not worrying" has been reported in other studies that have examined African Americans' responses to stress and various health problems (Boutain, 2001;Holt & McClure, 2006;Killoran, Schlitz, & Lewis, 2002;Silverman, Musa, Kirsch, & Siminoff, 1999).…”
Section: Discussionmentioning
confidence: 83%
“…Ongoing stressors combine to worsen heart health and cause increased distress that must be controlled by "not worrying." "Not worrying" has been reported in other studies that have examined African Americans' responses to stress and various health problems (Boutain, 2001;Holt & McClure, 2006;Killoran, Schlitz, & Lewis, 2002;Silverman, Musa, Kirsch, & Siminoff, 1999).…”
Section: Discussionmentioning
confidence: 83%
“…Only a small subset of 4 women of the 19 in this study described themselves as having moved on from their cervical cancer experience. Killoran et al (2002) described this process as normalizing the adversity experienced with cancer. Their qualitative study participants downplayed the significance of the cancer event in their lives, similar to that reported by the current study's subset.…”
Section: Discussionmentioning
confidence: 99%
“…They identified intimacy as an important factor in their sexual adjustment and stressed the importance of communication between healthcare professionals and patients with partners in improving outcomes. Killoran, schlitz, and lewis (2002) studied 17 survivors of different types of metastatic cancer. Participants described the impact of a life-threatening condition on their life stories.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Killoran et al [25], in another qualitative study, interviewed 17 long-term survivors of metastatic cancer and suggested that there are no real lessons to be learned from exceptional patients. Nearly all of the participants framed their unusual recovery as being largely unremarkable, without any major lessons to be learned or any recognition of having a transformational process leading to recovery (e.g., having "a wake up call").…”
Section: Discussionmentioning
confidence: 98%